Toxicological consultation data management system based on experience of Pomeranian Center of Toxicology - Piotr Maciej Kabata; Wojciech Waldman; Jacek Sein Anand (Nofer Institute of Occupational Medicine, 2015)
Background: In this paper the structure of poisonings is described, based on the material collected from tele-toxicology consults by the Pomeranian Center of Toxicology in Gdańsk and harvested from its Electronic Poison Information Management System. In addition, we analyzed conclusions drawn from a 27-month operation of the system. Material and Methods: Data were harvested from the Electronic Poison Information Management System developed in 2012 and used by the Pomeranian Center of Toxicology since then. The research was based on 2550 tele-toxicology consults between January 1 and December 31, 2014. Subsequently the data were electronically cleaned and presented using R programming language. Results: The Pomeranian voivodeship was the prevalent localisation of calls (N = 1879; 73.7%). Most of the calls came from emergency rooms (N = 1495; 58.63%). In the case of 1396 (54.7%) patients the time-lag between intoxication and the consult was less than 6 h. There were no differences in the age distribution between genders. Mean age was 26.3 years. Young people predominated among intoxicated individuals. The majority of intoxications were incidental (N = 888; 34.8%) or suicidal (N = 814; 31.9%) and the most of them took place in the patient's home. Conclusions: Information about Poison Control Center consultations access should be better spread among medical service providers. The extent of poison information collected by Polish Poison Control Centers should be limited and unified. This should contribute to the increased percentage of properly documented consultations. Additional duties stemming from the need of digital archiving of consults provided, require the involvement of additional staff, leading to the increased operation costs incurred by Poison Control Centers. Med Pr 2015;66(5):635-644